Strategi Guru Dalam Mengajar Siswa Berkesulitan Membaca dan Menulis di Kelas IV SD Negeri Burneh 3 - Olga Maharani; M. Fadlillah (Lembaga Pengembangan Kinerja Dosen, 2024)
The purpose of this research is to find out how the teacher's strategy and find out how the teacher's obstacles in teaching students with reading and writing difficulties in class IV SDN Burneh 3. This research is a descriptive qualitative research with the research subjects of class IV teachers and 2 students with reading and writing difficulties. Data collection in this study used observation, interview and documentation techniques. The data analysis in this study used the data analysis steps of the Miles and Hubermen model, namely data reduction, data presentation, and conclusion drawing. The results show that the teacher's strategy in teaching students with reading and writing difficulties is to use an expository learning strategy by utilizing learning media, learning resources, and learning methods that are different from other students, and using an individual approach, and providing special guidance to students with reading and writing difficulties. Teacher barriers in teaching students with reading and writing difficulties are: 1) Lack of support and cooperation from parents, 2) Lack of motivation from within the student, 3) Students' low memory.